Transthoracic echocardiography using second harmonic imaging with Valsalva manoeuvre for the detection of right to left shunts. - Clarke, N; Timperley, J; Kelion, A; Banning, A (2004)
AIMS: To assess transthoracic echocardiography (TTE) using second harmonic imaging with Valsalva manoeuvre compared to transesophageal echocardiography (TEE) for the diagnosis of right to left cardiac and pulmonary shunts. METHODS AND RESULTS: One hundred and ten patients referred for TEE underwent TTE with bubble contrast. Bubbles in the left atrium within three cardiac cycles were considered diagnostic for a patent foramen ovale (PFO) and later as a pulmonary shunt. Greater than 20 bubbles in the left atrium was considered a large shunt and less than 20 a small shunt. TEE was performed immediately afterwards and read blinded to the TTE results. Pick-up rates were similar with 19 TEE positive (13 PFO) and 18 TTE positive (14 PFO) patients. There were five TEE positive/TTE negative cases who had significantly poorer TTE image quality score (2.7 +/- 0.8 vs 1.9 +/- 0.6, p < 0.05). There were six TEE negative/TTE positive cases, two cases requiring Valsalva manoeuvre to become positive. The Valsalva manoeuvre significantly increased the number of bubbles shunting (10 +/- 11 vs 20 +/- 19, p < 0.005). CONCLUSION: TTE with Valsalva manoeuvre is as good as TEE in diagnosing shunts. Valsalva manoeuvre increases the size of shunt. Both techniques produce false negative results.